STUDY OF SOIL SLOPE REINFORCEMENT WITH SOIL NAILING METHOD USING IRONWOOD, CASE STUDY OF HAULING ROAD SLOPE IN PT CIPTA KRIDATAMA COAL MINE - Ihsan Bagaskoro, Dimas
Slope failure is a phenomenon that often occurs in open pit mines, both on pit slopes and backfill slopes. One of the most common types of slope failure is arc failure, which generally occurs on slopes composed of soil material, fracture rock masses, and weathered rock material. One way to prevent arc failure is by reinforcing the mine slope or changing the slope geometry. Ground nailing with wood material is one form of reinforcement commonly used on slopes in mining areas with soil material, especially on temporary excavation slopes. Besides being easily available, the use of wood can also reduce costs and is quite easy to implement. However until now there are not many guidelines that can be used in the installation of wood/timber nailing in the mining world, especially in Indonesia which has a variety of wood plants. This lack of guidelines has led to the installation of timber nailing on mine slopes sometimes not having a strong scientific basis and becoming ineffective. This study examines the effect of various geometry parameters for installing timber nailing on earthen mine slopes, including the spacing of timber nailing, and the geometry pattern to determine the best way to install the nailing. In the case of haul road side slopes, it was found that soil nailing using timber was done vertically, in rows parallel to the slope strike, with 5m spacing between nails and the timber used was ironwood. Recommendations for the installation of mine slope reinforcement with timber materials have also been made referring to the research case, including the calculation of safety factors on slopes using the Bishop method in slide 6.0, deformation analysis using RS 2 and comparison with the results of daily movement monitoring obtained from the shooting of monitoring prisms.